2016
DOI: 10.1073/pnas.1522663113
|View full text |Cite
|
Sign up to set email alerts
|

Slide-and-exchange mechanism for rapid and selective transport through the nuclear pore complex

Abstract: Nucleocytoplasmic transport is mediated by the interaction of transport factors (TFs) with disordered phenylalanine-glycine (FG) repeats that fill the central channel of the nuclear pore complex (NPC). However, the mechanism by which TFs rapidly diffuse through multiple FG repeats without compromising NPC selectivity is not yet fully understood. In this study, we build on our recent NMR investigations showing that FG repeats are highly dynamic, flexible, and rapidly exchanging among TF interaction sites. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(150 citation statements)
references
References 92 publications
12
131
0
3
Order By: Relevance
“…Our previous simulations demonstrated that FSFG motifs make multiple transient and exploratory contacts with the interaction surface of NTF2 (24). Taken together, the single binding mode detectable by SVD suggests that the exchange rates of FG motifs contacting the NTF2 surface are faster than the experimental detection (~ms) such that the observed CSPs reflect a single time-averaged binding mode.…”
Section: Resultsmentioning
confidence: 77%
“…Our previous simulations demonstrated that FSFG motifs make multiple transient and exploratory contacts with the interaction surface of NTF2 (24). Taken together, the single binding mode detectable by SVD suggests that the exchange rates of FG motifs contacting the NTF2 surface are faster than the experimental detection (~ms) such that the observed CSPs reflect a single time-averaged binding mode.…”
Section: Resultsmentioning
confidence: 77%
“…Finally, the remaining regions without an atomic representation ( i.e. , the predicted transmembrane and disordered regions) were represented by a flexible string of beads encompassing 25 to 100 residues each; the low-resolution representation of these regions is justified because their conformations are likely “decoupled” from the structure of the rest of the NPC 48,118 .…”
Section: Methodsmentioning
confidence: 99%
“…Each of the FG repeat domains was represented as a flexible string of beads; a bead had a radius of 6 Å and encompassed 20 residues to achieve a compromise between computational efficiency and accuracy 118,146149 . Consecutive beads were restrained by a bond with an equilibrium length of 18 Å and a constant force of 1.0 kcal/mol/Å, approximating the spring-like nature of flexible polymers 150 in general and FG repeat domains 118,147149,151153 in particular. The freely diffusing molecules included 1,600 NTRs and 1,600 inert macromolecules (0.33 mM each), each consisting of eight subgroups of 200 macromolecules, ranging in radius from 4 to 28 Å in 2 Å increments (10 to 75 kDa, assuming constant protein density of 1.38 g/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been combined with recent advances in MS instrument technology and complementary structural techniques, such as cryoelectron microscopy, to interrogate the structures of highly complex protein structures (Gaubitz et al, 2015; Greber et al, 2014; Lasker et al, 2012; Navare et al, 2015; Olson et al, 2014; Raveh et al, 2016). A seminal in silico study demonstrated that homology modeling could determine highly accurate structures when the modeling was combined with a sufficient density of distance constraints derived from chemical crosslinking (Leitner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%